Eko-Teologi dalam Kurikulum Adiwiyata: Strategi Integrasi Ekologi Islam dan Transformasi Perilaku Ekologis Siswa - Angga Perayuda; Reza Ahmad Zahid; Abbas Sofwan Matlail Fajar; Moch. Mukhlison; Diana Amalia (Journal of Islamic Education, 2026)
This study aims to analyze the integration of Islamic ecology as the basis of the Adiwiyata School curriculum at SMPN 5 Kota Kediri and its transformative impact on students' pro-environmental behavior. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using an interactive model (data reduction, display, and conclusion drawing). The results indicate that: (1) Eco-theological values (such as Tawhid, Khalifah, Ihsan, and anti-Fasad) are holistically integrated into general subjects and actualized in practical projects, including the production of eco-bricks, eco-printing, and pokja liquid fertilizer; (2) This theological internalization effectively overcomes cultural and structural barriers by shifting student motivation from extrinsic compliance (fear of school rules) to intrinsic-spiritual awareness (worship and divine mandate). The novelty of this research demonstrates that Islamic ecology can be inclusively operationalized in public secondary schools, deconstructing the binary separation between applied science and theology. In conclusion, an eco-theology-based Adiwiyata curriculum is crucial in shaping a persistent and sustainable pro-environmental habitus